ANALYZING THE VALUES OF ISLAM ON WEDDING TRADITIONS IN DOMPU, WEST NUSA TENGGARA - Ardian Ardian; Syahruddin Usman; Syamsuddin Syamsuddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This study focuses on the values of Islamic education contained in the customary marriage in Tembalae Village, Pajo District, Dompu Regency. Description of the focus of this research are the process of implementing traditional marriages in Tembalae village, Pajo sub-district, Dompu district and the values of Islamic education in marriage customs in Tembalae village, Pajo sub-district, Dompu district. The results of the research on marriage customs in Tembalae village through several stages: Firstly, stages before the marriage contract, a. panati (small meeting), b. wi,i Nggahi (application), c. Mbolo Weki (consultation ), d. Wa,a Co,i (delivery of dowry ), e. ziki map Kapanca (sticking henna leaves ). Secondly, stages of implementing the marriage contract, namely lafa (contract). Thirdly, the stages as difficult as the marriage contract are Jambuta Tekarne,e ( wedding party). The values of Islamic education contained in the marriage customs in Tembalae Village include the value of Aqidah education, the value of Worship education, and the value of moral education, which need to be developed and preserved.